Nitrogen-phosphorus-sulfur triple-doped hard carbon negative electrode material and preparation method and application thereof
By immersing the phosphorus source solution of the biomass precursor and high-temperature gas phase treatment, a three-doped hard carbon material of nitrogen, phosphorus and sulfur is formed, which solves the problem of insufficient performance of the negative electrode material of sodium ion battery, improves the efficiency and electrochemical performance of Coulomb, and realizes the Efficient use of resources and reduced costs.
Patent Information
- Application Number
- CN202411228915.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The existing lithium-ion battery anode materials are not suitable for sodium ion batteries, and the cost is high. The first-round Coulomb efficiency of hard carbon anode materials is not high, making it difficult to meet the high efficiency and long cycle life requirements of sodium ion batteries.
The biomass precursor is soaked through phosphorus source solution, high-temperature vapor deposition and nitrogen-containing, phosphorus-containing and sulfur-containing gas treatment to form a nitrogen-phosphorus-sulfur tri-doped hard carbon material, adjust the pore structure and functional groups of the material, and improve the embedding of sodium ions. Detachment kinetics and electrode reversibility.
It achieves high first-circuit Coulomb efficiency and excellent electrochemical performance of sodium ion batteries, reduces material costs, increases the added value of the negative electrode material, and promotes the practical application of sodium ion batteries.
Smart Images

Figure CN119240654A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of biomass utilization and new energy materials, and in particular to a nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles, fixed energy storage, and mobile devices, the market has put forward new requirements for high performance and low cost of batteries and battery materials. As important energy storage systems, lithium-ion batteries and sodium-ion batteries have the characteristics of high energy density, high charge and discharge efficiency, and high cycle stability. In batteries, the positive electrode material is the main determinant of battery energy. At the same time, the performance of the negative electrode material is also crucial to battery performance. Its capacity and the reversible insertion / extraction kinetics of lithium / sodium ions affect the overall performance of the whole battery. In order to meet the requirements of high efficiency, long cycle life, and low cost of batteries, the importance of developing new negative electrode materials has become increasingly prominent. The existing commercial lithium-ion battery negative electrode materials are mainly graphite and silicon carbon, but neither is suitable for sodium-ion batteries and does not have cost advantages. Therefore, finding alternative and sustainable sodium-ion battery negative electrode materials has become a hot topic of research.
[0003] Biomass is considered to be the most promising precursor for negative electrode materials of sodium ion batteries due to its low price, abundant resources, and the ability to form hard carbon materials through high-temperature pyrolysis and carbonization. At the same time, the comprehensive utilization of waste biomass resources can also alleviate environmental pressure and increase the added value of waste biomass, especially the residue (oil residue) left after oil extraction from seed crops, which is usually used as animal feed or microbial culture medium with low added value. The main components of oil residue are cellulose and protein, rich in nitrogen and sulfur. At the same time, this type of biomass precursor is treated with an external phosphorus source, and the capillary effect brought by its own rich cellulose component can be used to achieve The uniform and sufficient mixing of the precursor and the phosphorus source and the carbonization treatment are beneficial to obtaining nitrogen, phosphorus and sulfur tri-doped carbon materials. In addition, by introducing nitrogen-containing, phosphorus-containing and sulfur-containing atmospheres for heat treatment, the oxygen-containing functional groups that are unfavorable to the reversibility and coulombic efficiency of the battery can be partially replaced by nitrogen-containing, phosphorus-containing and sulfur-containing functional groups. This nitrogen, phosphorus and sulfur doping treatment of the carbon negative electrode material can adjust and improve the affinity of sodium ions and the negative electrode material. At the same time, phosphorus and sulfur, due to their larger atomic radius, are also beneficial to expand the interlayer spacing of the hard carbon material, which is beneficial to the insertion and extraction of sodium ions. While improving the kinetics of the sodiumization process, it can also improve the reversibility of the electrode material and obtain higher coulombic efficiency. Summary of the invention
[0004] The present invention provides a method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material, which solves the problem of low first-cycle coulomb efficiency of the existing hard carbon negative electrode and the problem of high added value utilization of biomass waste.
[0005] In order to solve this technical problem, the present invention provides the following technical solution:
[0006] A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material comprises the following steps:
[0007] S1: crushing the hard carbon negative electrode material biomass precursor and passing it through a 100-500 mesh sieve;
[0008] S2: soaking the sieved hard carbon negative electrode material biomass precursor in a phosphorus source solution for no less than 1 hour, then centrifuging or filtering, and vacuum drying;
[0009] S3: placing the dried biomass precursor into a high-temperature atmosphere furnace and introducing inert gas protection, heat treating at 900-1500°C for 1-5 hours. At the end of the heat treatment, additionally introducing a certain proportion of organic small molecule gas relative to the inert atmosphere for 1-10 minutes, the organic small molecule gas undergoes high-temperature vapor deposition, and deposits the carbon formed by the decomposition of small molecules in the micropores and mesopores of the hard carbon formed by the decomposition of the macromolecular components in the biomass precursor, thereby regulating the pore structure of the hard carbon material;
[0010] S4: After the high temperature heat treatment time in the previous step is completed, the temperature is controlled to drop to 250-400°C by program control, and a certain proportion of nitrogen-containing, phosphorus-containing, and sulfur-containing gases relative to the inert atmosphere are additionally introduced for heat treatment for 1-3 hours to partially replace the oxygen-containing functional groups in the carbon material formed by pyrolysis with nitrogen-containing, phosphorus-containing, and sulfur-containing functional groups. The tail gas in this process is first introduced into an alkaline solution, then into an acid solution, and finally into water;
[0011] S5: The carbon material obtained by pyrolysis is placed in a strong alkaline solution for washing and heating. The treatment time is not less than 2 hours and the temperature does not exceed 100°C. After the treatment is completed, it is repeatedly washed with water and filtered or centrifuged until it is neutral. After vacuum drying, the nitrogen, phosphorus and sulfur doped hard carbon negative electrode material is obtained.
[0012] The beneficial effects of adopting the above technical solution are as follows: (1) the biomass precursor is crushed and then sieved to obtain a precursor powder with a concentrated particle size distribution, which is beneficial to the uniform absorption of the phosphorus source solution by the capillary action of the precursor during the phosphorus source solution treatment, and the uniform precursor particles are also beneficial to obtaining a hard carbon material with a concentrated particle size distribution after high-temperature carbonization. The concentrated distribution of the particle size is beneficial to obtaining a negative electrode sheet with uniform quality and thickness after the hard carbon material is subjected to roller treatment in the preparation of the negative electrode sheet;
[0013] (2) The biomass precursor contains a high cellulose content and has a capillary effect. The inorganic or organic phosphorus source solution is easily absorbed into the precursor. After separation, the biomass precursor that absorbs the phosphorus source can be obtained. Since the biomass precursor is pre-crushed and sieved, the uniform absorption of the phosphorus source in the biomass precursor can be guaranteed, which is conducive to the uniform doping of phosphorus in the hard carbon material during the further heat treatment and carbonization process.
[0014] (3) The biomass precursor treated with phosphorus source is subjected to high-temperature heat treatment. Since the biomass precursor used is rich in protein components, the high-temperature heat treatment carbonization process is conducive to the nitrogen and sulfur doping of the carbon material. A relatively high heat treatment temperature is used in this process. At the same time, due to the introduction of phosphorus, it plays an inducing and promoting role in the crystallization of the carbon material during the high-temperature carbonization of the biomass precursor. Therefore, the high heat treatment temperature and the introduction of phosphorus source are conducive to obtaining a closed-cell nitrogen-phosphorus-sulfur doped hard carbon material with a low specific surface area. The contact area with the electrolyte is small, and the side reactions on the surface of the material during the battery process are few, resulting in a high first-cycle coulomb efficiency. In addition, phosphorus and sulfur have a large atomic radius. The introduction of the two doping is conducive to expanding the interlayer spacing of the hard carbon material, which is more conducive to the reversible insertion and extraction of sodium ions. When matched with the positive electrode material to form a full battery, the capacity of the positive electrode material can be maximized, and it has a broader practical application prospect.
[0015] (4) During the high-temperature pyrolysis and carbonization of the biomass precursor, organic small molecule gases are introduced. Under high temperature, the organic small molecules enter the void structure of the hard carbon material and undergo cracking and carbonization, filling the micropores and mesopores of the hard carbon material. By controlling the types of different organic small molecules, the proportion of relatively inert atmosphere, and the treatment time, the pore structure and specific surface area of the hard carbon material can be regulated, thereby achieving adjustable microstructure of the hard carbon material. The adjustable microstructure can also bring about adjustable performance of the hard carbon negative electrode material.
[0016] (5) The oxygen-containing functional groups in hard carbon materials have too high binding energy with sodium ions, which makes it difficult for sodium ions bound to the active sites of oxygen-containing functional groups during the electrochemical process to be removed, resulting in irreversible sodium storage, which is not conducive to the coulombic efficiency of hard carbon negative electrode materials. However, by using nitrogen-, phosphorus-, and sulfur-containing gases to treat the carbon materials formed by pyrolysis, some of the oxygen-containing functional groups on the surface of the materials can be replaced by nitrogen-, phosphorus-, and sulfur-containing functional groups. The binding energy of these three functional groups with sodium ions is in a moderate range, which makes it easy to bind to sodium ions without making it difficult to remove sodium ions, thus leading to reversible storage of sodium ions. Therefore, this replacement of oxygen-containing functional groups can effectively improve the reversibility of hard carbon negative electrode materials and obtain higher first-cycle coulombic efficiency.
[0017] (6) The tail gas generated after treating the carbon material formed by pyrolysis with nitrogen-, phosphorus- and sulfur-containing gases is first passed into an alkaline solution, then into an acid solution, and finally into water. This tail gas treatment method can remove unreacted ammonia, phosphine and hydrogen sulfide gases. By passing the tail gas into an alkaline solution, the two acidic gases phosphine and hydrogen sulfide can be removed first, and then by passing the tail gas into an acid solution, the remaining ammonia can be removed. Finally, by passing the tail gas into water, the remaining trace ammonia, phosphine and hydrogen sulfide, as well as the solute components in the acid solution that may overflow can be removed. In addition, the method of first passing the alkaline solution and then the acid solution can also prevent the large-scale overflow of the solute components of the acid solution that may be caused by the high-temperature tail gas contacting the acid solution.
[0018] (7) Since the energy barrier required for doping phosphorus into carbon materials is relatively high and the reaction kinetics is relatively slow, the phosphorus source introduced in the present invention will not completely bond with the carbon material under high temperature conditions and be doped into the carbon material, and the excess undoped phosphorus source will exist as an impurity, which will inevitably be detrimental to the electrochemical properties of the carbon material. Therefore, the remaining phosphorus source needs to be removed. The remaining phosphorus source may exist in the form of phosphorus element, phosphorus oxide, phosphide, phosphate, etc., and the strong alkaline solution will react with phosphorus element and phosphorus oxide to dissolve the phosphorus element and phosphorus oxide that may be produced. The phosphide will be hydrolyzed and dissolved when it comes into contact with water. At the same time, phosphate is mainly water-soluble sodium phosphate. Therefore, the carbon material obtained by treating with a strong alkaline solution can completely remove the residual phosphorus element, phosphorus oxide, phosphide, phosphate, etc. that may exist therein, and at the same time, it will not react with the doped phosphorus that has been bonded to the carbon, while maintaining the phosphorus doping amount of the carbon material and removing the unfavorable phosphorus-containing residual impurities, thereby obtaining a high-quality nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material.
[0019] Preferably, the biomass precursor is the residue left after oil is extracted from seed crops, including one or more of cottonseed meal, palm meal, pepper seed meal, tung seed meal, litsea cubeba meal and oil-sand soybean meal.
[0020] The beneficial effects of adopting the above technical scheme are as follows: (1) The residues left after oil extraction from seed crops such as cottonseed meal, palm meal, pepper seed meal, tung nut meal, litsea cubeba meal and oil bean meal have high protein content, which makes it easier to form nitrogen and sulfur-doped hard carbon materials during high-temperature heat treatment and carbonization; (2) The cellulose content in this type of biomass precursor is high, and the overall theoretical carbon content is high, which is conducive to ensuring a high carbon yield; (3) This type of biomass precursor has a large output, narrow existing uses and low added value. It is only used as animal feed or microbial culture medium, and the price is generally 2,000 to 3,000 yuan / ton, while the hard carbon negative electrode material prepared by using it currently has a market price of 100,000 yuan / ton, which has the advantage of high added value.
[0021] Preferably, the phosphorus source solution is selected from an aqueous solution of phosphoric acid, sodium phosphate, phytic acid, sodium phytate, sodium pyrophosphate, sodium tripolyphosphate, and a carbon tetrachloride solution of triphenyl phosphate, phenylphosphonic acid, phosphorus trichloride, and phosphorus pentachloride, and the concentration is 0.1 mol / L to 5 mol / L.
[0022] The beneficial effects of the above technical solution are as follows: (1) when using this type of inorganic or organic phosphorus source solution to treat a biomass precursor, since the main component of the precursor is cellulose, it has a capillary effect and can absorb the phosphorus source into the biological tissue of the precursor, which is beneficial to the incorporation of phosphorus during high-temperature heat treatment and obtains phosphorus-doped hard carbon materials; (2) since the biomass precursor must be centrifuged or filtered after treatment with the phosphorus source solution, the amount of phosphorus source solute remaining in the biomass precursor is limited, and the phosphorus source in the phosphorus source solution is extremely excessive, the prepared phosphorus source solution only needs to be supplemented with a very small amount of phosphorus source solute and can be reused.
[0023] Preferably, the heating rate of the heat treatment is 5-10°C / min before 400°C, and is 0.5-5°C / min after 400°C.
[0024] The beneficial effects of adopting the above technical solution are as follows: the temperature range of 400-500°C is the temperature range in which the biomass precursor has the fastest decomposition and carbonization rate. Before this temperature, in order to improve the heat treatment efficiency and reduce the time cost, it is necessary to carry out the process at a faster heating rate; after reaching the temperature range of 400-500°C, the biomass will decompose rapidly, producing a large amount of carbon oxide gas and water vapor, and the heating rate should be slowed down after the temperature reaches 400°C, which can avoid the rapid expansion of the material caused by the large amount of gas generated due to excessive decomposition, which will be ejected from the container and cause contamination of the furnace and the material. Problem; at the same time, after the biomass is carbonized in the temperature range of 400-500°C, further heating it to a higher temperature at a slow heating rate is conducive to the formation of a short-range ordered and long-range disordered characteristic structure of hard carbon materials. If the initial faster heating rate is still maintained during this process, the carbon material will crystallize too quickly, which is not conducive to the formation of a short-range ordered structure. The obtained carbon material cannot fully provide a place for sodium ions to embed when used as the negative electrode of a sodium ion battery, resulting in a decrease in capacity. The above technical scheme takes into account the economy of heat treatment, prevention of pollution of hard carbon materials, and optimization of performance of hard carbon materials.
[0025] Preferably, the additionally introduced organic small molecule gas is selected from one of methane, ethane, acetylene and liquefied petroleum gas, and accounts for 0.5% to 3% of the volume of the inert gas.
[0026] The beneficial effects of adopting the above technical scheme are as follows: organic small molecule gases such as methane, ethane, acetylene, and liquefied petroleum gas are all cheap and easily available gases. Due to their small molecular weight, they are easy to enter the micropores and mesopores, and they will all undergo cracking at the pyrolysis and carbonization temperature of the hard carbon material used in the present invention. After these organic small molecules entering the micropores and mesopores of the hard carbon are cracked and carbonized, they will fill the micropores and mesopores of the hard carbon material. By controlling the types of different organic small molecules, the proportion of relatively inert atmosphere, and the treatment time, the pore structure and specific surface area of the hard carbon material can be regulated, thereby achieving the adjustable microstructure of the hard carbon material, and then bringing about the adjustable performance of the hard carbon negative electrode material.
[0027] Preferably, the nitrogen-containing gas is ammonia, the phosphorus-containing gas is phosphine, and the sulfur-containing gas is hydrogen sulfide, wherein ammonia uses finished gas, phosphine is obtained by hydrolysis of aluminum phosphide, or by thermal decomposition of sodium hypophosphite, and hydrogen sulfide is obtained by hydrolysis of sodium sulfide, or by thermal decomposition of dimethyl sulfoxide, and the volume proportion of the ammonia gas to the inert gas is 5% to 30%.
[0028] The beneficial effects of the above technical solution are as follows: ammonia, phosphine and hydrogen sulfide gases have high reaction activity at high temperature and can react with some oxygen-containing functional group sites on the surface of hard carbon materials. However, due to the high binding energy of oxygen-containing functional groups with sodium ions, it is difficult for sodium ions bound to the active sites of oxygen-containing functional groups during the electrochemical process to be removed, resulting in irreversible sodium storage, which is not conducive to the coulomb efficiency of hard carbon negative electrode materials. The carbon material formed by pyrolysis is treated with nitrogen-containing, phosphorus-containing and sulfur-containing gases, which can replace some oxygen-containing functional groups on the surface of the material with nitrogen-containing, phosphorus-containing and sulfur-containing functional groups. These three The binding energy between the functional group and the sodium ion is in a moderate range, which is easy to bind to the sodium ion but not difficult to remove the sodium ion, which can bring about the reversible storage of the sodium ion. Therefore, the replacement of the oxygen-containing functional group can effectively improve the reversibility of the hard carbon negative electrode material and obtain a higher first-cycle coulomb efficiency. In addition, since phosphine and hydrogen sulfide gases are not easy to store for a long time, the present invention uses sodium sulfide hydrolysis or dimethyl sulfoxide thermal decomposition to prepare fresh hydrogen sulfide gas, and uses aluminum phosphide hydrolysis or sodium hypophosphite thermal decomposition to prepare fresh phosphine gas, which is prepared and used immediately, solving the storage problem of phosphine and hydrogen sulfide gases.
[0029] Preferably, the strong alkaline solution is selected from an aqueous solution of sodium hydroxide and potassium hydroxide, and the concentration is 1 mol / L to 20 mol / L.
[0030] The beneficial effect of adopting the above technical solution is that after introducing a phosphorus source for phosphorus doping, a phosphorus-doped hard carbon negative electrode material can be obtained, but there may be excess phosphorus that has not been doped into the carbon material, which may have an adverse effect on battery performance. The use of a strong alkaline solution and heated washing treatment can remove possible residual impurities such as phosphates, phosphides, elemental phosphorus, etc.
[0031] The carbon material obtained by the preparation method of the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material can be applied to the application of sodium ion battery negative electrode material.
[0032] The beneficial effects of the above technical solution are as follows: when the preparation method of the nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material of the present invention is used, the protein components rich in the biomass precursors cottonseed meal, palm meal, pepper seed meal, tung seed meal, litsea cubeba meal and oil bean meal are helpful for nitrogen and sulfur doping of the carbon material during high-temperature carbonization, while the treatment of the phosphorus source is beneficial for phosphorus doping of the carbon material during high-temperature carbonization. The two can cooperate to realize the preparation of nitrogen-phosphorus-sulfur tri-doped hard carbon material. The introduction of organic small molecules can cause their cracking and carbonization in the void structure of the hard carbon material, thereby regulating the pore structure, and the nitrogen-, phosphorus- and sulfur-containing gases The high temperature treatment can partially replace the oxygen-containing functional groups that are unfavorable to the reversibility of the hard carbon negative electrode material with nitrogen-containing, phosphorus-containing, and sulfur-containing functional groups, thereby improving the Coulomb efficiency of the hard carbon negative electrode. In addition, phosphorus and sulfur have larger atomic radii, which are also beneficial to expand the interlayer spacing of the hard carbon material and facilitate the insertion and extraction of sodium ions. This carbon material has good electrochemical properties when used as the negative electrode of sodium ion batteries. At the same time, the high heat treatment temperature and the induction and promotion of the crystallization of carbon materials by phosphorus during the high-temperature carbonization of the biomass precursor are conducive to obtaining closed-pore hard carbon materials with low specific surface area (specific surface area ≤10m 2 / g), this hard carbon material has a high specific surface area (specific surface area ≥ 100m 2 / g), it has a small contact area with the electrolyte, and fewer side reactions occur on the material surface during the battery process, so the reversibility is greatly improved. The first-cycle coulomb efficiency is much higher than that of the porous hard carbon material with a high specific surface area. The high first-cycle coulomb efficiency is beneficial to the practical application of the negative electrode material. When it is matched with the positive electrode material to form a full battery, the irreversible sodium loss is small, which is beneficial to maximizing the capacity of the positive electrode material.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) Resource recycling and added value improvement: The present invention uses the residue left after oil extraction from low-value-added seed crops as a precursor, and utilizes the rich nitrogen and sulfur elements in the residue as well as the additional phosphorus element to obtain nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode materials through high-temperature pyrolysis and carbonization, turning waste into treasure, achieving effective resource recycling, reducing waste generation and environmental impact, and greatly improving added value;
[0035] (2) Efficient preparation of hard carbon negative electrode materials: Through a unique pyrolysis carbonization process and a nitrogen-phosphorus doping process, while ensuring a carbon yield greater than 40%, the present invention successfully prepares nitrogen-phosphorus-sulfur doped hard carbon materials. This method can efficiently convert oil pressing residues of seed crops such as cottonseed meal, palm meal, pepper seed meal, tung seed meal, litsea cubeba meal and oil bean meal into nitrogen-phosphorus-sulfur doped hard carbon materials, providing high-quality negative electrode materials for the preparation of sodium ion batteries;
[0036] (3) Improving battery performance: The prepared hard carbon negative electrode material has a nitrogen, phosphorus and sulfur doped structure, which provides abundant active sites, regulates and improves the affinity between sodium ions and negative electrode materials, expands the interlayer spacing of hard carbon materials, and improves the kinetics of the sodiumization process. At the same time, high heat treatment temperature, the induction and promotion of the crystallization of carbon materials by phosphorus during the high-temperature carbonization of biomass precursors, and the cracking and carbonization of small organic molecules in the hard carbon pores are conducive to obtaining closed-cell hard carbon materials with low specific surface area, reducing irreversible electrochemical side reactions on the surface of hard carbon negative electrodes. Combined with the replacement of oxygen-containing functional groups by nitrogen-containing, phosphorus-containing and sulfur-containing functional groups, high first-cycle coulomb efficiency can be obtained, which is conducive to maximizing the capacity of the positive electrode material when matched with a full battery.
[0037] (4) The hard carbon negative electrode material obtained by the present invention can be applied to sodium ion batteries to obtain excellent electrochemical performance at 300 mA g -1 The specific capacity reaches 350 mAh g at a current density of -1 The coulombic efficiency of the first cycle reached more than 80%; by obtaining stable and excellent electrochemical properties, it laid the foundation for the further industrial production of sodium ion battery negative electrode materials prepared from crop oil pressing residues. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0039] Figure 1 This is a flow chart of the preparation method of the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material of the present invention;
[0040] Figure 2 The scanning electron microscope images of different scales of the nitrogen, phosphorus and sulfur tri-doped hard carbon material prepared in Example 1;
[0041] Figure 3 The scanning electron microscope images of the carbon material prepared in Comparative Example 1 at different scales;
[0042] Figure 4 Comparison of the first cycle constant current charge and discharge of the sodium ion battery assembled in Example 8 and Comparative Example 2;
[0043] Figure 5Comparison of the 10th cycle constant current charge and discharge of the assembled sodium ion batteries of Example 8 and Comparative Example 2. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0045] Example 1
[0046] A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material, such as Figure 1 As shown, the following steps are included:
[0047] S1: crushing cottonseed meal with a crusher and collecting it after passing it through a 325-mesh sieve;
[0048] S2: soaking the collected crushed cottonseed meal in a 1 mol / L phytic acid solution for 1 hour, filtering and separating after the treatment, and vacuum drying the treated cottonseed meal solids;
[0049] S3: placing the dried cottonseed meal into a high-temperature atmosphere furnace, and introducing an inert gas protection, heat treating at a temperature of 1300° C. for 2 hours. At the end of the heat treatment, additionally introducing liquefied petroleum gas at a volume of 1% relative to the inert atmosphere for 5 minutes to obtain a carbon material;
[0050] S4: After the high temperature heat treatment time in the previous step is completed, the temperature is lowered to 350°C by program control, and 10% of ammonia, phosphine and hydrogen sulfide gas relative to the volume of the inert atmosphere is additionally introduced for heat treatment for 2 hours, and the tail gas is first introduced into an alkaline solution, then into an acid solution, and finally into water;
[0051] S5: The carbon material obtained by pyrolysis is placed in a 6 mol / L sodium hydroxide solution for washing and heating for 2 hours at a temperature of 80°C. After the treatment, it is repeatedly washed with water and filtered or centrifuged until neutral. After vacuum drying, a nitrogen, phosphorus and sulfur doped hard carbon negative electrode material is obtained.
[0052] Example 2
[0053] A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material comprises the following steps:
[0054] S1: crushing cottonseed meal with a crusher and collecting it after passing it through a 325-mesh sieve;
[0055] S2: soaking the collected crushed cottonseed meal in a 0.5 mol / L phytic acid solution for 1 hour, filtering and separating after the treatment, and vacuum drying the treated cottonseed meal solids;
[0056] S3: placing the dried cottonseed meal into a high-temperature atmosphere furnace, and introducing an inert gas protection, heat treating at 900° C. for 2 hours. At the end of the heat treatment, additionally introducing liquefied petroleum gas at a volume of 1% relative to the inert atmosphere for 5 minutes to obtain a carbon material;
[0057] S4: After the high temperature heat treatment time in the previous step is completed, the temperature is lowered to 350°C by program control, and 10% of ammonia, phosphine and hydrogen sulfide gas relative to the volume of the inert atmosphere is additionally introduced for heat treatment for 2 hours, and the tail gas is first introduced into an alkaline solution, then into an acid solution, and finally into water;
[0058] S5: The carbon material obtained by pyrolysis is placed in a 6 mol / L sodium hydroxide solution for washing and heating for 2 hours at a temperature of 80°C. After the treatment, it is repeatedly washed with water and filtered or centrifuged until neutral. After vacuum drying, a nitrogen, phosphorus and sulfur doped hard carbon negative electrode material is obtained.
[0059] Example 3
[0060] A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material comprises the following steps:
[0061] S1: crushing cottonseed meal with a crusher and collecting it after passing it through a 325-mesh sieve;
[0062] S2: soaking the collected crushed cottonseed meal in a 3 mol / L phytic acid solution for 1 hour, filtering and separating after the treatment, and vacuum drying the treated cottonseed meal solids;
[0063] S3: placing the dried cottonseed meal into a high-temperature atmosphere furnace, and introducing an inert gas protection, heat treating at 1500° C. for 2 hours. At the end of the heat treatment, additionally introducing liquefied petroleum gas at a volume of 1% relative to the inert atmosphere for 5 minutes to obtain a carbon material;
[0064] S4: After the high temperature heat treatment time in the previous step is completed, the temperature is lowered to 350°C by program control, and 10% of ammonia, phosphine and hydrogen sulfide gas relative to the volume of the inert atmosphere is additionally introduced for heat treatment for 2 hours, and the tail gas is first introduced into an alkaline solution, then into an acid solution, and finally into water;
[0065] S5: The carbon material obtained by pyrolysis is placed in a 6 mol / L sodium hydroxide solution for washing and heating for 2 hours at a temperature of 80°C. After the treatment, it is repeatedly washed with water and filtered or centrifuged until neutral. After vacuum drying, a nitrogen, phosphorus and sulfur doped hard carbon negative electrode material is obtained.
[0066] Example 4
[0067] A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material comprises the following steps:
[0068] S1: crushing cottonseed meal with a crusher and collecting it after passing it through a 500-mesh sieve;
[0069] S2: soaking the collected crushed cottonseed meal in a 3 mol / L phytic acid solution for 1 hour, filtering and separating after the treatment, and vacuum drying the treated cottonseed meal solids;
[0070] S3: placing the dried cottonseed meal into a high-temperature atmosphere furnace and introducing an inert gas for protection, heat treating at 1300° C. for 2 hours. At the end of the heat treatment, additionally introducing 1% acetylene relative to the volume of the inert atmosphere for 5 minutes to obtain a carbon material;
[0071] S4: After the high temperature heat treatment time in the previous step is completed, the temperature is lowered to 250°C by program control, and 20% of ammonia, phosphine and hydrogen sulfide gas relative to the volume of the inert atmosphere are additionally introduced for heat treatment for 2 hours, and the tail gas is first introduced into an alkaline solution, then into an acid solution, and finally into water;
[0072] S5: The carbon material obtained by pyrolysis is placed in a 3 mol / L potassium hydroxide solution for washing and heating for 2 hours at a temperature of 80°C. After the treatment, it is repeatedly washed with water and filtered or centrifuged until neutral. After vacuum drying, a nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material is obtained.
[0073] Example 5
[0074] The difference between this embodiment and embodiment 1 is that palm meal, chili seed meal, tung nut meal, litsea cubeba meal or soybean meal are used as biomass precursors for treatment instead of cottonseed meal in embodiment 1.
[0075] Example 6
[0076] The difference between this embodiment and embodiment 1 is that an aqueous solution of phosphoric acid, sodium phosphate, phytic acid, sodium phytate, sodium pyrophosphate or sodium tripolyphosphate, or a carbon tetrachloride solution of triphenyl phosphate, phenylphosphonic acid, phosphorus trichloride or phosphorus pentachloride is used instead of the phytic acid solution in embodiment 1 as a phosphorus source for treatment.
[0077] Example 7
[0078] The difference between this embodiment and embodiment 1 is that methane, ethane and acetylene are used to replace the small molecule organic gas in embodiment 1 for treatment.
[0079] Example 8
[0080] In this embodiment, the carbon material prepared by the method in Example 1 was used as the working electrode, metallic sodium was used as the counter electrode to assemble a sodium ion battery, a glass fiber diaphragm was used as the diaphragm, and 1M NaClO 4 The electrolyte was prepared by dissolving ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 and adding 5 wt% fluoroethylene carbonate. The assembled battery was -1 The charge and discharge tests were carried out at the current density.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that no phosphorus source is used to treat the biomass precursor.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 8 is that the carbon material prepared by the method in Comparative Example 1 is used as the working electrode.
[0085] The materials obtained in Example 1 and Comparative Example 1 were characterized. Figure 2 The scanning electron microscope images of different scales of the nitrogen, phosphorus and sulfur tri-doped hard carbon material prepared in Example 1 show that the carbon material has a special pore structure, and the pores show a special layered structure;
[0086] Attached Figure 3 The scanning electron microscope images of the carbon material prepared in Comparative Example 1 at different scales show that the carbon material is in the form of loose irregular particles, and no obvious pore structure is observed;
[0087] Attached Figure 4 The first cycle constant current charge and discharge comparison of the sodium ion battery assembled in Example 8 and Comparative Example 2 shows that the first cycle charge capacity of the sodium ion battery assembled in Example 8 is 340 mAh g -1 The first cycle coulombic efficiency reached 83%, which is much higher than that of comparative example 2, where the assembled sodium ion battery only showed 215 mAh g -1 The first-cycle charging specific capacity and the first-cycle Coulomb efficiency are only 61%.
[0088] Since the sodium ion battery assembled in Example 8 uses the nitrogen, phosphorus and sulfur tri-doped hard carbon material prepared in Example 1, and the sodium ion battery assembled in Comparative Example 2 uses the non-phosphorus doped carbon material prepared in Comparative Example 1, combined with the attached Figure 2 and attached Figure 3Comparison of the morphologies of the two carbon materials shows that the nitrogen, phosphorus and sulfur tri-doped hard carbon material obtained by introducing phosphorus source treatment is beneficial to the storage of electrolyte in the material due to its special pore structure and special layered structure in the pores. It can also shorten the migration path of sodium ions and make sodium ion migration easier. The nitrogen, sulfur and phosphorus doping treatment can adjust and improve the affinity of sodium ions and negative electrode materials, while improving the kinetics of the sodiumization process, it can also improve the reversibility of the electrode material and obtain a higher coulombic efficiency, thus obtaining a higher specific capacity and first-cycle coulombic efficiency.
[0089] Attached Figure 5 This is a comparison of the 10th cycle constant current charge and discharge of the sodium ion batteries assembled in Example 8 and Comparative Example 2. It can be seen from the figure that the nitrogen, phosphorus and sulfur tri-doped hard carbon material prepared in Example 1 used in the sodium ion battery assembled in Example 8 shows a longer low potential platform during the reversible charge and discharge process, indicating that the nitrogen, phosphorus and sulfur tri-doped hard carbon material prepared in Example 1 involves more sodium ion embedding / de-embedding behavior, while the carbon material prepared in Comparative Example 1 used in the sodium ion battery assembled in Comparative Example 2 has a shorter low potential platform during the reversible charge and discharge process, and the capacity contribution is mostly in the inclined platform region, indicating that the carbon material prepared in Comparative Example 1 involves more capacitance contribution; the above results indicate that phosphorus doping and the special material morphology it brings about jointly affect the electrochemical behavior of the material.
[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a nitrogen-phosphorus-sulfur tri-doped hard carbon negative electrode material, characterized in that: The following steps are involved: S1: crushing the hard carbon negative electrode material biomass precursor and passing it through a 100-500 mesh sieve; S2: soaking the sieved hard carbon negative electrode material biomass precursor in a phosphorus source solution for no less than 1 hour, then centrifuging or filtering, and vacuum drying; S3: placing the dried biomass precursor into a high-temperature atmosphere furnace and introducing inert gas protection, heat treating at 900-1500°C for 1-5 hours. At the end of the heat treatment, additionally introducing a certain proportion of organic small molecule gas relative to the inert atmosphere for 1-10 minutes, the organic small molecule gas undergoes high-temperature vapor deposition, and deposits the carbon formed by the decomposition of small molecules in the micropores and mesopores of the hard carbon formed by the decomposition of the macromolecular components in the biomass precursor, thereby regulating the pore structure of the hard carbon material; S4: After the high temperature heat treatment time in the previous step is completed, the temperature is controlled to drop to 250-400°C by program control, and a certain proportion of nitrogen-containing, phosphorus-containing, and sulfur-containing gases relative to the inert atmosphere are additionally introduced for heat treatment for 1-3 hours to partially replace the oxygen-containing functional groups in the carbon material formed by pyrolysis with nitrogen-containing, phosphorus-containing, and sulfur-containing functional groups. The tail gas in this process is first introduced into an alkaline solution, then into an acid solution, and finally into water; S5: The carbon material obtained by pyrolysis is placed in a strong alkaline solution for washing and heating. The treatment time is not less than 2 hours and the temperature does not exceed 100°C. After the treatment is completed, it is repeatedly washed with water and filtered or centrifuged until it is neutral. After vacuum drying, the nitrogen, phosphorus and sulfur doped hard carbon negative electrode material is obtained.
2. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: The biomass precursor is the residue left after oil is extracted from seed crops, including one or more of cottonseed meal, palm meal, pepper seed meal, tung seed meal, litsea cubeba meal or oil-sand soybean meal.
3. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the phosphorus source solution is an aqueous solution of phosphoric acid, sodium phosphate, phytic acid, sodium phytate, sodium pyrophosphate or sodium tripolyphosphate, and one of triphenyl phosphate, phenylphosphonic acid, phosphorus trichloride and phosphorus pentachloride in carbon tetrachloride, and the concentration of the phosphorus source solution is 0.1 mol / L to 5 mol / L.
4. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: In the step S3, the heating rate of the heat treatment is 5-10°C / min before 400°C, and 0.5-5°C / min after 400°C.
5. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: The type of the organic small molecule gas additionally introduced in step S3 is one of methane, ethane, acetylene and liquefied petroleum gas, and its volume ratio relative to the inert gas is 0.5% to 3%.
6. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: In step S4, the nitrogen-containing gas is ammonia, the phosphorus-containing gas is phosphine, and the sulfur-containing gas is hydrogen sulfide, wherein the ammonia uses finished gas, the phosphine is obtained by hydrolyzing aluminum phosphide, or by thermal decomposition of sodium hypophosphite, and the hydrogen sulfide is obtained by hydrolyzing sodium sulfide, or by thermal decomposition of dimethyl sulfoxide, and the volume proportion relative to the inert gas is 5% to 30%.
7. The method for preparing the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 1, characterized in that: In step S5, the strong alkaline solution is an aqueous solution of sodium hydroxide or potassium hydroxide, and the concentration is 1 mol / L to 20 mol / L.
8. A nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material obtained by the preparation method of a nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to any one of claims 1 to 7.
9. Use of the nitrogen, phosphorus and sulfur tri-doped hard carbon negative electrode material according to claim 6 in negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Method for treating artificial graphite scraps
CN106395812A
N-doped porous carbon material prepared from bean dregs and preparation method and application of material
CN110304620A
Element-doped biomass hard carbon negative electrode material for sodium-ion battery, preparation method and sodium-ion battery
CN110571432A
Preparation method and application of coal-based functional carbon material
CN117623274A
Preparation method and application of gradient sub-nanopore structure hard carbon material
CN117800318A
Cited By
Preparation method and application of phosphorus-doped porous carbon
CN120136100A
Preparation method and application of phosphorus-doped porous carbon
CN120136100B
Phosphorus-doped biomass-based hard carbon material, negative electrode, sodium ion battery and preparation method
CN121063515A
Method for preparing biomass-based hard carbon material under assistance of oil gas and application of biomass-based hard carbon material
CN121735243A
Battery and electrical device
WO2026194468A1